Evaluating four typical fibers used for OGFC mixture modification regarding drainage, raveling, rutting and fatigue resistance. (30th August 2020) - Zhang, Jiawei; Huang, Weidong; Zhang, Yuan; Lv, Quan; Yan, Chuanqi
Highlights: 4 commonly used fibers were investigated and polyester is recommended. Adding fibers improves the overall OGFC mixture performance. Lignin fiber has little tensile strength and shows the least mechanical improvement. Excessive fiber causes agglomeration during mixing and leads to inferior performance. Abstract: Fiber is an essential additive used in asphalt mixture due to its asphalt absorption and reinforcement characteristics, especially for Open-Graded Friction Course (OGFC) mixture. However researches about the influence of varying fibers types on OGFC mixture are not adequate. In this study, 4 typical fibers, namely lignin fiber, basalt fiber, polyester fiber, and polyacrylonitrile fiber were evaluated. Their raw material sources, appearance and physical properties were compared. Also, resultant mixture drainage property, raveling resistance, rutting resistance, stiffness and fatigue life were evaluated using Schellenberg binder drainage test, Cantabro test, Hamburger Wheel Tracking test, and Four-Point-Bending test, respectively. Different fiber contents (0.15%, 0.3% and 0.45%) were considered. Results show that fiber modification improves the mixture overall performance, but the improvement notably differs between fiber types. Lignin fiber has a small density, which renders it the best improvement on mixture drainage property. But lignin fiber has little tensile strength and shows the least improvement on OGFC mixture mechanical properties. The other three fibers are strong filaments that can physically crosslink with each other and demonstrate better performance than lignin fiber. Polyester fiber exhibits the best improvement and thus is recommended. Increasing the fiber content does not necessarily facilitate the improvement due to the agglomeration issue during mixing. An optimal fiber content exists for each fiber type, which is 0.3%, 0.15%, 0.3%, and 0.15% for lignin fiber, basalt fiber, polyester fiber, and polyacrylonitrile fiber, respectively.